Perception of Teachers on Using ICT in Classroom in Context of Kailali District - Shrestha, Suman (Journal of Durgalaxmi, 2022)
This paper aims to present perception of teacher on using ICT ((information, communication and technology) in classroom in context of Kailali district. For the purpose of the survey, ten teachers teaching in secondary level were selected and questionnaire was used to collect data. The findings of the research show that even though majority of the teachers are equipped with electronic gadgets like laptop and desktop computers and have access to the reliable internet both in school and at home, they cannot use ICT in their teaching because of lack of sufficient knowledge about web-based and game-based teaching tools and they have not received training related to ICT use in the classroom teaching.